Pseudohypoparathyroidism type 1A and Albright hereditary osteodystrophy: a comprehensive review of molecular pathogenesis, clinical manifestations, and therapeutic approaches - Gálvez, Galilea L.; Roblero, Jesus E. G. (International Journal of Research in Medical Sciences, 2025)
Pseudohypoparathyroidism type 1A (PHP1A) is a rare genetic disorder characterized by end-organ resistance to parathyroid hormone (PTH) due to heterozygous inactivating mutations in the GNAS gene. Patients frequently exhibit the phenotypic features of Albright hereditary osteodystrophy (AHO), including short stature, brachydactyly, subcutaneous ossifications, and obesity. Despite advances in molecular genetics, the clinical management of PHP1A remains challenging due to its multisystemic involvement. This review aims to elucidate the molecular mechanisms underlying PHP1A, delineate its clinical and biochemical characteristics, and discuss current and emerging therapeutic strategies. A systematic literature review was conducted, analyzing peer-reviewed articles from PubMed, Scopus, and OMIM databases focusing on PHP1A, AHO, and related disorders. PHP1A arises from maternal transmission of GNAS mutations, leading to impaired Gsα protein function and subsequent hormonal resistance. The AHO phenotype is present in most cases, with additional endocrine abnormalities such as hypothyroidism and growth hormone deficiency commonly reported. Early diagnosis is essential to mitigate complications, including severe hypocalcemia and neurocognitive impairments. Treatment involves calcium and vitamin D supplementation, though targeted therapies remain under investigation. PHP1A with AHO represents a complex multisystem disorder necessitating a multidisciplinary approach. Further research into genotype-phenotype correlations and novel therapeutic interventions is warranted to improve patient outcomes.